Scénarios d’accidents occasionnés par une perturbation du mouvement dans les secteurs de la construction et de la métallurgie. Pour une prévention locale et diversifiée - Sylvie Leclercq; Faiza Abdat; Xavier Cuny; Claire Tissot (Perspectives Interdisciplinaires sur le Travail et la Santé)
The prevention of injuries caused by collisions, slips, or any other movement disturbance at work represents a major challenge. 143 written accounts of accidents in the construction and metallurgy sectors were analyzed using a Bayesian approach to extract recurrent scenarios. These accounts were characterized by 30 generic factors followed by 8 recurrent scenarios. Movement disturbances most often occurred when the worker was manipulating an object. They can be explained, in particular, by the occurrence of technical incidents and the presence of coactivities or constraints related to collective work, which emphasizes the role of work organization. Depending on the occupational sector considered, the identified factors/scenarios were sometimes more present in one sector than the other, sometimes less so, and sometimes absent altogether. Our results confirm the need for local, diversified prevention that combines production and safety rationales and that strives for a balance between a defensive conception of safety and increased system resilience.